Integration of advanced oxidation processes (ozone/magnetite) and biological treatments (up-flow anaerobic sludge blanket reactor - uasb and microalgae) for the treatment of landfill leachates (2025)
This research addresses the treatment of landfill leachates by integrating advanced oxidation processes (AOPs) and biological treatments to enhance contaminant removal efficiency and reduce effluent toxicity. For this purpose, catalytic ozonation with magnetite, its coupling with an up-flow anaerobic sludge blanket (UASB) reactor, and the integration of microalgae as a post-treatment stage were evaluated. Experimental studies were conducted using leachates from two landfills with contrasting characteristics: one located in a municipality with predominantly agricultural activities (La Madera, Ocaña) and another in a city with industrial activity (El Guayabal, Cúcuta), allowing for a broader application of the results. The study determined that catalytic ozonation with magnetite optimizes organic matter degradation and improves leachate biodegradability, achieving chemical oxygen demand (COD) reductions of 85.3% in El Guayabal and 75.8% in La Madera. Process optimization established optimal operating conditions with an ozone dose of 6 g/h, a magnetite concentration of 2.5 g/L, and a pH of 9, maximizing process efficiency while minimizing ozone consumption. However, a progressive decrease in catalyst efficiency was observed after successive reuse cycles, highlighting the need for regeneration strategies to maintain performance. The coupling of catalytic ozonation with the UASB reactor improved the stability of the biological system, increasing the BOD₅/COD ratio from 0.26 to 0.38 in El Guayabal and from 0.23 to 0.32 in La Madera, facilitating the anaerobic biodegradation of organic matter. The UASB reactor, operating at a hydraulic retention time of 24 hours, achieved COD removals between 60% and 75%, with more excellent stability in leachates with higher concentrations of biodegradable compounds. However, ammoniacal nitrogen removal was limited, with residual concentrations reaching up to 546.1 mg/L, indicating the need for additional treatment to comply with discharge standards. Microalgae as a post-treatment allowed for the removal of up to 65% of total nitrogen and 70% of phosphorus, demonstrating its potential as a final stage in landfill leachate treatment. However, its efficiency in organic matter removal was lower tan that of the UASB reactor, suggesting that its application should focus primarily on nutrient reduction and improving final effluent quality. This study's conclusions confirm that combining catalytic ozonation with magnetite, anaerobic treatment, and microalgae is a viable and efficient alternative for treating landfill leachates with different characteristics. The treatment configuration plays a crucial role in overall process efficiency, with catalytic ozonation being more effective as a pretreatment to facilitate subsequent biological degradation. The need to integrate additional nitrogen removal and catalyst regeneration strategies is emphasized, and the economic and energy feasibility of the process for large-scale implementation is assessed. From a scientific perspective, this thesis contributes to advancing knowledge in landfill leachate treatment by developing optimization models for catalytic ozonation, evaluating catalyst stability during reuse cycles, studying the impact of ozonation on leachate biodegradability, and demonstrating the synergy between advanced oxidation processes and biological systems.